Analisis Kelayakan Pengembangan Unit Usaha Pengolahan Hasil Perikanan pada Bidang Usaha Milik Pesantren di Pondok Pesantren Salafiyah Syafi’iyah Sukorejo (Feasibility Analysis of Developing Fishery Product Processing Business Units in The Islamic Boarding School Business Sector at The Salafiyah Syafi'iyah Sukorejo Islamic Boarding School) - Jazila, Ismi; Ramli, Ramli; Sawiyah, Sawiyah; Junianingsih, Ika (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabay, 2025)
Islamic boarding schools have a great opportunity to develop a business including fishery product processing businesses. Social capital in the form of students, alumni and the surrounding community are potential consumers for businesses developed by Islamic boarding schools. One of the large Islamic boarding schools in East Java is the Salafiyah Safi'iyah Islamic boarding school in Situbondo Regency. Safiah Safi'iyah can develop a fishery product processing business under the auspices of the Islamic Boarding School Business Sector (BUMP). The development of a fishery product processing business under BUMP must be preceded by a business feasibility analysis. Therefore, it is necessary to conduct research on